EVALUASI HAK DAN KEWAJIBAN DALAM PELAYANAN KESEHATAN PRIMER: TINJAUAN LITERATUR - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
This study aims to evaluate the regulation and implementation of rights and obligations in primary health care in Indonesia through a literature review. The results of the study indicate that national regulations have established patients' rights to quality care, clear information, privacy protection, and the right to consent to or refuse medical treatment. On the other hand, patients also have obligations to provide accurate information, comply with medical instructions, and respect the rights of healthcare workers. Healthcare workers themselves are entitled to legal protection and professional development, as well as the obligation to provide services in accordance with professional standards and maintain patient confidentiality. However, implementation on the ground still faces challenges such as lack of understanding of regulations, limited resources, and weak supervision and socialisation. Therefore, sustained efforts are needed in the form of education, strengthening the capacity of healthcare workers, and improving the supervision system to ensure that the balance between rights and responsibilities in primary healthcare services is optimally realised.